Rheological behaviour of cement mortars reinforced with acrylic fibres - Oliveira, Luiz Antonio Pereira de (2018)
The fibre reinforcement efficacy of mortar is dependent upon many factors, including the properties of the matrix as well as the fibre geometry, size, type, volume and dispersion. Among the plastic fibres typically used in mortars, little or nothing is known about the rheological behaviour of acrylic fibres. Thus, in this study the influence of different acrylic fibres characteristics on the rheological behaviour of cement mortars was investigated. The method selected is based on factorial design of experiments in which the parameters considered are the length, diameter and acrylic fibre content. The test results indicate that Herschel-Bulkley model better simulate the rheological behaviour of acrylic fibres reinforced mortars. It was also observed that the yield stress increases with the reduction of fibre length and diameter and the plastic viscosity increases as the fibre length increases.